A Hybrid Supercapacitor based on Porous Carbon and the Metal‐Organic Framework MIL‐100(Fe). Issue 7 (11th June 2014) - Campagnol, Nicolò; Romero‐Vara, Ricardo; Deleu, Willem; Stappers, Linda; Binnemans, Koen; De Vos, Dirk E.; Fransaer, Jan
Abstract Composite supercapacitor electrodes based on carbon nanotubes, carbon black, and a metal–organic framework with iron(III) coordination centers [MIL‐100(Fe), MIL‐88B(Fe), or MIL‐53(Fe)] were prepared and tested with several aqueous electrolytes. A correlation between hydrated ion size and the electric response of the electrodes was found, which sheds light on how these materials work as energy‐storage devices. MIL‐100(Fe) shows the most promising results, and the capacitance obtained with the samples in the solutions used is higher than that of a mixture of carbon and nanotubes in the same solution. Unfortunately, shortcomings due to reductive dissolution still hamper the long‐term cyclability of the electrodes.